(untitled) (Bangladesh Journal of Child Health, 2010)
Background: Perinatal asphyxia is the most important preventable cause of cerebral injury in the neonatal period leading to very high neonatal mortality and morbidity in developing countries. Little can be done for a baby affected by severe perinatal asphyxia. So, prevention is unquestionably desired. Objective: To identify the maternal and fetal risk factors for the development of birth asphyxiated babies and to see the short term outcome of the affected babies. Methods: An analytical type of or observational study was done in the Special Care Baby Unit (SCBU) of Dhaka Medical College Hospital from October 2003 to March 2004. Identification of the risk factors was done by retrospective comparison of the cases and controls. Outcome was analyzed by cross sectional comparative study. One hundred consecutive cases of birth asphyxia, admitted in SCBU, were enrolled in the study. Another 30 neonates admitted during this period for other reasons (i.e., jaundice, septicemia, low birth weight) were taken as control. Necessary information were collected by detailed history taking, clinical examination and close follow up of the hospital course, using pre-designed questionnaire and recording form. Results: Male: female ratio 3:2 both in the cases and controls. Mean age on admission was 13.8 hours and 2.6 days for case and control respectively. Identified important maternal risk factors were primiparity (57% in cases vs. 33.3% in control), hypertension (16.6% vs. 3.3%), pre-eclamptic toxemia of pregnancy (24% vs. 13.3%), prolonged rupture of membrane (33.3% vs. 6.7%), prolonged labour (34% vs. 3.3%) and use of oxytocin during labour (16% vs. none). All these were statistically significant (p<0.05). Serious neonatal complications noted among the asphyxiated babies were convulsion, hypoxic ishchemic encephalopathy and necrotizing enterocolitis. These were not seen among the control group. Mortality among the asphyxiated babies was 16% during hospital stay, whereas no fatality was recorded among the control. Neurological sequelae was observed in 28% of asphyxiated babies but was absent in controls. Conclusion: All the identified risk factors as well as neonatal complications were significantly higher in asphyxiated babies. Most of these could have been prevented even with our limited resources. Key words: Birth Asphyxia; risk factors; immediate outcome. DOI: 10.3329/bjch.v33i3.5688 Bangladesh Journal of Child Health 2009; Vol.33(3): 83-89